Pengembangan Media Pembelajaran S-MATCHA Terintegrasi Keislaman untuk Meningkatkan Literasi Matematis Siswa SMP - Pramono, Yasmine Az Zahra Awwalina; Harithiya, Avida Faustina; Chusna, Febri Lailatul; Karina, Lisa Amelia; Huda, Nuril; Rahmawati, Laili (SAP (Susunan Artikel Pendidikan), 2025)
The low mathematical literacy of students, particularly in statistics, poses a challenge in mathematics education. This study aims to develop an interactive gamification-based learning media, S-MATCHA (Statistic from Mathematics of Gacha), which integrates Islamic values to enhance students' mathematical literacy. The research employs a Research and Development (R&D) method using the ASSURE model, which includes analyzing student characteristics, formulating learning objectives, selecting methods and media, as well as implementation and evaluation. This media focuses on data collection topics such as mean, median, mode, and range. The effectiveness of the media was tested through a limited experiment involving ninth-grade students at MTsN Kota Batu, utilizing a pre-test and post-test design. The validity results indicate that S-MATCHA is highly suitable for use, with average scores of 89.15% from subject matter experts, 97.3% from media experts, and 95% from practitioners. The practicality of the media was also rated very well. Experimental results showed an improvement in students' mathematical literacy, with an N-Gain score of 0.45, which falls into the moderate category. These findings suggest that S-MATCHA is effective in supporting learning and providing meaningful experiences through the integration of Islamic values, making it an innovative alternative for context-based mathematics education.